Transcription Analysis of the Chemerin Impact on Gene Expression Profile in the Luteal Cells of Gilts - Makowczenko, Karol G. (Genes (Basel), 2020)
Chemerin is a recently discovered adipokine that participates in the regulation of many physiological and disorder-related processes in mammals, including metabolism, inflammatory reactions, obesity, and reproduction. We investigated how chemerin affects the transcriptome profile of porcine luteal cells. The luteal cells were acquired from mature gilts. After the in vitro culturing with and without chemerin, the total RNAs were isolated and high-throughput sequencing was performed. Obtained datasets were processed using bioinformatic tools. The study revealed 509 differentially expressed genes under the chemerin influence. Their products take part in many processes, important for the functions of the corpus luteum, such as steroids and prostaglandins synthesis, NF-κB and JAK/STAT signal transducing pathways, and apoptosis. The expression of the CASP3, HSD3B7, IL1B, and PTGS2 genes, due to their important role in the physiology of the corpus luteum, was validated using the quantitative real-time polymerase chain reaction (qPCR) method. The qPCR confirmed the changes of gene expression. Chemerin in physiological concentrations significantly affects the expression of many genes in luteal cells of pigs, which is likely to result in modification of physiological processes related to reproduction.